(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper sets a methodology for motivating multinational organizations to work together in an atmosphere of international collaboration. We propose that there is an effort for e-intermediary between buyers and suppliers to work together so that the buyers and suppliers can work together. We expect this method, through a selection of order quantities and price penalties by market intermediaries, to enable the optimal choice of supply capability by market intermediaries.